Testing the efficacy of a brief-caries risk assessment form to evaluate the dental health status among preschool children, Bangkok, Thailand - Saruta Saengtipbovorn (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - The study aims to test the efficacy of brief-caries risk assessment form with standard caries risk assessment form and to evaluate the application of caries risk assessment following American Academy of Pediatric Dentistry (AAPD) between brief and standard caries risk assessment on dental health status among preschool children. Design/methodology/approach - Brief-caries risk assessment form was developed. Then, experimental study was conducted in public health center 54 among 70 patients (35 test and 35 control) from January to July 2019. Test group used brief-caries assessment form, and control group used standard form. Both groups received the same caries risk assessment criteria and management protocol from AAPD. At baseline, 3-month and 6-month follow-up, caries risk and dental health status (plaque index, cavitated caries lesion and non-cavitated caries lesion) were assessed. Data were analyzed by descriptive statistic, t-test, chi-square test, Fisher's exact test and repeated measures ANOVA. Findings - Percentage of high caries risk decreased from baseline (93.9%: test and 96.9%: control) to 6-month follow-up (66.7%: test and 65.6%: control) in both groups, with no statistically significant differences between groups. Plaque index, cavitated caries lesion and non-cavitated caries lesion were not statistically significant differences between groups. Brief-caries assessment decreased times/visit from 10-15 minutes to 5 minutes. Originality/value - Brief-caries assessment form decreased caries risk and prevented dental caries as the standard form. Using brief-caries assessment form could save time, is cost-effective and is appropriate for use in public health centers. However, a short follow-up time might have insufficient power to detect the differences between groups.